Rectal perforation caused by a self-inserted foreign body: a case report - Sanjay, R.; Bargee, Rajendra; Panwar, Pradeep; Kumar, Prashant (International Surgery Journal, 2021)
Rectal foreign bodies have a storied history as a part of anorectal trauma. Objects encountered are most commonly household objects consisting of bottles and glasses. Other objects include tooth brushes, deodorant bottles, food articles, knives, sports equipment, cell phones, flash lights, wooden rods, broom sticks, sex toys including dildos and vibrators, light bulbs, nails, or other construction tools, christmas ornaments, aerosol canisters, cocaine packets, and many more. The reasons for insertion in decreasing order of frequency are autoeroticism, concealment, attention-seeking behavior, accidental, assault and to alleviate constipation. Here we presented a case of 32 years old presented to the ER with complaints of pain in lower abdomen and anal region for 12 hours. He complained of severe pain when he tried to defecate. He gave history of self-insertion of an empty drug vial into his rectum. Rectal foreign bodies represent a challenging and unique field of colorectal trauma. The important factors in dealing with these patients are careful history and physical examination. Patients are often embarrassed about this condition and may conceal the truth. So, a high index of suspicion is required to accurately diagnose.